2019
DOI: 10.3390/nu11112774
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Patients Show Lower Bioavailable 25(OH)D and 1,25(OH)2D, but No Difference in Ratio of 25(OH)D/24,25(OH)2D and FGF23 Concentrations

Abstract: Vitamin D (VitD) insufficiency is common in multiple sclerosis (MS). VitD has possible anti-inflammatory effects on the immune system. The ratio between VitD metabolites in MS patients and the severity of the disease are suggested to be related. However, the exact effect of the bone-derived hormone fibroblast-growth-factor-23 (FGF23) and VitD binding protein (VDBP) on this ratio is not fully elucidated yet. Therefore, the aim is to study differences in total, free, and bioavailable VD metabolites and FGF23 bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 90 publications
(138 reference statements)
1
11
0
Order By: Relevance
“…But observational studies showed inconsistent results. A recent cohort study including 91 MS patients didn’t find any difference ( p = 0.65) between MS patient and healthy controls in plasma FGF23 concentrations ( 36 ). Another cohort study including 14 relapsing-remitting MS (RRMS) patients also found that FGF23 concentrations in MS patients were comparable to controls ( p = 0.59) ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
“…But observational studies showed inconsistent results. A recent cohort study including 91 MS patients didn’t find any difference ( p = 0.65) between MS patient and healthy controls in plasma FGF23 concentrations ( 36 ). Another cohort study including 14 relapsing-remitting MS (RRMS) patients also found that FGF23 concentrations in MS patients were comparable to controls ( p = 0.59) ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that vitamin D plays a role in innate and specific immunity by regulating T lymphocytes; at the same time, studies have shown that vitamin D can not only affect the proliferation and maturation of T cells, but also reduce the expression of IL-17, promote the proliferation of Treg cells and enhance their immune tolerance [15,16] . Kevin et al [17] , Tedeschi et al [18] and Volt et al [19] detected that the downstream genes regulated by VDR are related to systemic lupus erythematosus and multiple sclerosis. Studies of Hau et al [20] , and Jeffery et al [21] showed that the therapeutic effect of 1.25(OH) 2 D 3 in rheumatoid arthritis and psoriasis was related to IL-17A.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that 25(OH)D 3 status should be assessed with regard to DBP concentration to determine the free fraction [11]. Only three studies have previously analyzed the free portion of 25(OH)D 3 as a risk marker for MS, and their results are diverging [12][13][14]. These studies included relatively few cases (n = 76, 91, and 77, respectively) and used samples drawn after diagnosis of MS or clinically isolated syndrome, which confers the risk of reverse causality.…”
Section: Introductionmentioning
confidence: 99%